2004
DOI: 10.4049/jimmunol.172.7.4444
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Specific CD8+ T Cells Exhibit Markedly Reduced Levels of Bcl-2 and Bcl-xL

Abstract: Human immunodeficiency virus-specific CD8+ T cells are highly sensitive to spontaneous and CD95/Fas-induced apoptosis, and this sensitivity may impair their ability to control HIV infection. To elucidate the mechanism behind this sensitivity, in this study we examined the levels of antiapoptotic molecules Bcl-2 and Bcl-xL in HIV-specific CD8+ T cells from HIV-infected individuals. Bcl-2 expression was markedly decreased in HIV-specific CD8+ T cells compared with CMV-specific and total CD8+ T cells from HIV-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 74 publications
9
58
0
Order By: Relevance
“…A vital issue in the apoptosis field is the relative ratio between proand antiapoptotic factors that critically affect a cell's survival. 151 Similarly, we found downregulated levels of Bcl-2 in SIV-specific CD8 þ T cells from SIV-infected rhesus monkeys, which also exhibit increased apoptosis (YM Mueller, C Petrovas and PD Katsikis, unpublished data).…”
Section: Toward Understanding the Molecular Mechanism Of Hiv-specificmentioning
confidence: 66%
See 4 more Smart Citations
“…A vital issue in the apoptosis field is the relative ratio between proand antiapoptotic factors that critically affect a cell's survival. 151 Similarly, we found downregulated levels of Bcl-2 in SIV-specific CD8 þ T cells from SIV-infected rhesus monkeys, which also exhibit increased apoptosis (YM Mueller, C Petrovas and PD Katsikis, unpublished data).…”
Section: Toward Understanding the Molecular Mechanism Of Hiv-specificmentioning
confidence: 66%
“…153 Our data revealed that such a compensatory mechanism is impaired in HIV-specific CD8 þ T cells, 151 potentially priming them to apoptosis. On the other hand, CMV-specific CD8 þ T cells from HIV-infected patients are characterized by increased levels of Bcl-x L , 151 likely making them less sensitive to apoptosis, in agreement with our previous data. 61 Interestingly, total CD4 þ T cells from HIV-infected patients express comparable Bcl-2 levels with CD4 þ T cells from healthy individuals.…”
Section: Toward Understanding the Molecular Mechanism Of Hiv-specificmentioning
confidence: 74%
See 3 more Smart Citations